3-2x(x+1)=x-2

Simple and best practice solution for 3-2x(x+1)=x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3-2x(x+1)=x-2 equation:


Simplifying
3 + -2x(x + 1) = x + -2

Reorder the terms:
3 + -2x(1 + x) = x + -2
3 + (1 * -2x + x * -2x) = x + -2
3 + (-2x + -2x2) = x + -2

Reorder the terms:
3 + -2x + -2x2 = -2 + x

Solving
3 + -2x + -2x2 = -2 + x

Solving for variable 'x'.

Reorder the terms:
3 + 2 + -2x + -1x + -2x2 = -2 + x + 2 + -1x

Combine like terms: 3 + 2 = 5
5 + -2x + -1x + -2x2 = -2 + x + 2 + -1x

Combine like terms: -2x + -1x = -3x
5 + -3x + -2x2 = -2 + x + 2 + -1x

Reorder the terms:
5 + -3x + -2x2 = -2 + 2 + x + -1x

Combine like terms: -2 + 2 = 0
5 + -3x + -2x2 = 0 + x + -1x
5 + -3x + -2x2 = x + -1x

Combine like terms: x + -1x = 0
5 + -3x + -2x2 = 0

Factor a trinomial.
(1 + -1x)(5 + 2x) = 0

Subproblem 1

Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1

Subproblem 2

Set the factor '(5 + 2x)' equal to zero and attempt to solve: Simplifying 5 + 2x = 0 Solving 5 + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 2x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 2x = 0 + -5 2x = 0 + -5 Combine like terms: 0 + -5 = -5 2x = -5 Divide each side by '2'. x = -2.5 Simplifying x = -2.5

Solution

x = {1, -2.5}

See similar equations:

| -x+4x+1=3x-1+2 | | -2x+2x+4=3x-2x+2 | | 6-8x-3=-39+6x-14 | | 80+x=180 | | -9(x-7)-6=57 | | -20-9b+1=16b+20 | | 2(6x+5)=3x-26 | | 3-19p=-18p+20 | | -6w-12+2w=28 | | (10/3)/(2/21) | | -4/-5y=72 | | -3m=-6-5m | | 52/650 | | (1/4x-6)=(2/3x+3) | | 4u=3u-8 | | 2[3x-(4x-8)]=5(x-8) | | 3x+15=11+5x | | -7x+16=8(5x+2) | | -8p=176 | | 4(x+2)/6 | | 3+5(-8a-1)=-6-(3a-4) | | 0.15-0.01(x+1)=-0.03(2-x) | | (-2x/11)=66 | | 7x+3=2(3x+1)-x+8 | | x+6=15-x | | 13/6+x=6 | | 16n^2-8n-15=0 | | 2x-5y=4x+15 | | 5/2x=3/2x-4 | | 35x^4-2x^2-1=0 | | 14w-18=94 | | 9(x+6)+5=59 |

Equations solver categories